Trends in Women’s Leadership of Oncology Clinical Trials - Waldhorn, Ithai; Dekel, Ayelet; Morozov, Anna; Alon, Elisa Sardas; Stave, Danielle; Tsrooya, Noam Ben; Schlosser, Shir; Markel, Gal; Bomze, David; Meirson, Tomer (Frontiers in Oncology, 2022)
It is widely reported that women are underrepresented in leadership positions within academic medicine. This study aimed to assess women representation as principal investigators (PIs) in oncology clinical trials and characterize trends in women leadership. The gender of the PI was assessed using an API tool for predicting gender based on first names, and was determine for 39,240 (94.2%) investigators. In total, 11,516 (27.7%) women served as PI. Over the past 20 years, we found a decrease in the gap in gender representation of women PIs. Analysis by geographic distribution revealed more female representation among PIs in North America and Europe compared to Asia. Study sponsorship affected women's representation as well, as academic-funded trials were associated with higher female representation than industry-funded trials (31.4% vs. 18.8%, P<0.001). There was a significant correlation between the clinical trial phase and proportions of women PIs, where late phases were led by fewer women compared to early phase trials (P<0.001). In addition, an association between the PI’s gender and women enrollment in clinical trials was found (50% vs. 43% female participants, P<0.001). Taken together, women comprise a growing proportion of PIs in cancer clinical trials. Women leadership is more prevalent in western countries, early phase trials, and governmental-funded studies. This data can serve for the development of strategies to increase women's representation and monitor progress toward gender equality in PIs of cancer clinical trials.